Health Surveillance Assistants’ Practices of Postnatal Care in Lilongwe District, Malawi - Pindani, Mercy; Phiri, Chrissie; Chilinda, Idesi; Chikazinga, Wanangwa; Botha, Janet; Chorwe-Sungani, Genesis (Africa Journal of Nursing and Midwifery, 2020)
Health surveillance assistants (HSAs) participate in the provision of postnatal care in Malawi, although their knowledge and skills in maternal and reproductive health are limited. This article presents the findings of a mixed-methods study that was conducted in three selected health centres to document the practices of HSAs in the provision of postnatal care to mothers and babies in Lilongwe district in Malawi. A random sample of 97 HSAs participated in the quantitative part of this study and 30 of these participated in the qualitative aspect of the study. Quantitative data were analysed using descriptive statistics while qualitative data were analysed using thematic analysis. This study found that many respondents (>60%) had limited capacity to provide adequate postnatal care and 85.3% of them never checked the vital signs of mothers and babies. They also lacked knowledge and skills in some aspects of postnatal care including danger signs. Almost all the respondents (96.8%) had never received any training in Basic Emergency Obstetric and Neonatal Care (BEmONC), or Emergency Obstetric and Neonatal Care (EmONC). Considering that HSAs have limited capacity to provide postnatal care to mothers and their babies, shifting tasks of nurses or midwives to HSAs should not be considered as an “outright solution” for increasing access to postnatal care in low-resource settings because it may compromise the quality of care.